HUBUNGAN ANTARA DIABETES MELITUS TIPE 2 DAN SKOR LESI KALSIFIKASI BERDASARKAN PEMERIKSAAN INTRAVASCULAR ULTRASOUND (IVUS) PADA PASIEN PENYAKIT ARTERI KORONER - Aninka Saboe; Dendi Pudji Wahyudi; Eliza Techa Fattima; Achmad Fauzi Yahya (Jurnal Kardiologi Indonesia, 2026)
Background: Coronary artery calcification reflects the chronic burden of atherosclerosis and contributes to procedural complexity during Percutaneous Coronary Intervention (PCI). While coronary calcium has been extensively studied using Computed Tomography (CT), data on Intravascular Ultrasound (IVUS)-derived calcium characteristics in Southeast Asian populations remain limited. The Southeast Asian population, particularly Indonesians, may exhibit distinct patterns of atherosclerosis influenced by genetic, lifestyle, and metabolic factors. Therefore, we sought to investigate the association between cardiovascular risk factors and IVUS-derived total coronary calcium score in an Indonesian population. Methods: This single-center, retrospective observational study included consecutive patients who underwent IVUS-guided PCI between January 2020 and December 2021. Data on patient demographics and cardiovascular risk factors were obtained from medical records. The IVUS calcium scores recorded in the database were independently reanalyzed and validated by an experienced interventional cardiologist to ensure consistency and accuracy. Associations between cardiovascular risk factors and total IVUS calcium score were assessed using Spearman's rank correlation and the Kruskal–Wallis test.Results: A total of 111 patients were included in this study with a mean age of 61.3 ± 10.2 years; 72.1% were male. Hypertension was present in 60.4%, DM in 45.0%, dyslipidemia in 38.7%, and active smoking in 40.5%. The mean IVUS total calcium score was 1.93 ± 1.41. Among individual risk factors, dyslipidemia (ρ = 0.22, p = 0.021) and smoking (ρ = −0.24, p = 0.009) were significantly associated with calcium score. Patients with ≥2 risk factors had higher mean calcium scores (2.15 ± 1.35) compared with those with ≤1 risk factor (1.15 ± 1.33; p = 0.028). Conclusion: The total IVUS calcium score correlated significantly with the presence of dyslipidemia in this Indonesian population. A cumulative increase in cardiovascular risk factors was associated with greater coronary calcium burden, suggesting that multifactorial risk exposure plays an important role in coronary calcification in this population.